2017
DOI: 10.1021/acs.organomet.7b00670
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Electron Poor Cationic Triazoliumylidene N-Heterocyclic Carbene: Experimental and Computational Studies

Abstract: The electronic properties of the long-known cationic 1,2,4-triazoliumylidene 3a have been determined. The 77Se NMR chemical shift of its Se adduct 9 (δ = 138 ppm) indicates that 3a is only moderately π-acidic. M­(CO)2Cl complexes of 3a (M = Rh, Ir) allowed the IR spectroscopic determination of a TEP value of 2073 cm–1, the highest value known to date for a N-heterocyclic carbene (NHC). The properties of cationic 3a were compared to those of the related neutral triazolylidene 5, which was prepared for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…An additional reason might be the better mesomeric stabilization of the anionic charge. A comparison of the HOMO/LUMO energies of the cationic NHC derived from imidazo[4,5‐ b ]pyridinium, of the 13 series reported here, of the reference NHC 1,3‐dimethylimidazol‐2‐ylidene, and the conjugated anionic sydnone carbene is displayed in Figure . These examples of NHCs cover the range from extremely π‐electron poor to extremely π‐electron rich.…”
Section: Resultsmentioning
confidence: 99%
“…An additional reason might be the better mesomeric stabilization of the anionic charge. A comparison of the HOMO/LUMO energies of the cationic NHC derived from imidazo[4,5‐ b ]pyridinium, of the 13 series reported here, of the reference NHC 1,3‐dimethylimidazol‐2‐ylidene, and the conjugated anionic sydnone carbene is displayed in Figure . These examples of NHCs cover the range from extremely π‐electron poor to extremely π‐electron rich.…”
Section: Resultsmentioning
confidence: 99%
“…The diverse carbene-related transformations highlight the indispensable role of carbene in organic synthesis, which also implies that the contributions from computational studies are highly appreciated. , Previous computational studies of metal carbene-mediated X–H insertion (X = C, N, O, etc. ) and olefin metathesis have shown that theoretical calculations can enable a better mechanistic understanding of carbene chemistry. A summary of recent advances in theoretical studies would provide critical guidance for metal carbene formation and enlighten the rational design of new metal carbene transformation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017 César synthesized a cationic imidazolylidene NHC with an ammonium tag attached directly to the imidazole core [ 28 ]. Finally, in the same year Ganter described a triazoliumylidene with the formal +1 charge incorporated into the five-membered ring [ 29 ]. Several complexes formed by these carbenes have been also described, however, no ruthenium complexes with such carbenes have been synthesized.…”
Section: Introductionmentioning
confidence: 99%